Angiosarcoma: a systematic review of biomarkers in diagnosis, prognosis, and therapeutic strategies - Luong, Huyen Thuc Tran; Vercammen, Sofie; de Marco, Ario; de Rooster, Hilde; Cosma, Antonio (Frontiers in Oncology, 2025)
Angiosarcoma is a rare, aggressive vascular malignancy characterized by rapid proliferation, early metastasis, and limited therapeutic options, resulting in poor prognosis. The etiopathogenesis of AS remains elusive and diagnosis is challenging due to its similarity to other vascular lesions. This systematic review aims to synthesize existing literature on biomarkers in human AS tissue, encompassing genomic alterations, metabolic pathway changes, specific protein, and their implications for diagnosis, prognosis, and therapy. Eighty-seven studies were identified as meeting predefined eligibility criteria following a systematic search of Pubmed and Embase between 1996 and 2024. The review highlights recurrent mutations (e.g., TP53, POT1, MYC, PTPRB, KDR), altered metabolic pathways (VEGF, ANGPT-TIE, PI3K/Akt/mTOR, MAPK/ERK), and diverse protein expression patterns (e.g., ERG, CD31, CD34, vWF). These biomarkers underscore the complex molecular landscape of AS and offer potential targets for improved diagnostic, prognostic, and therapeutic strategies. This review provides a foundation for further research and the development of novel diagnostic and therapeutic approaches for this challenging malignancy.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251019523, identifier (CRD420251019523).